Historical perspectives on contemporary human–environment dynamics in southeast Africa. Issue 2 (28th January 2019) - Douglass, Kristina; Walz, Jonathan; Quintana Morales, Eréndira; Marcus, Richard; Myers, Garth; Pollini, Jacques
Abstract: The human communities and ecosystems of island and coastal southeast Africa face significant and linked ecological threats. Socioecological conditions of concern to communities, governments, nongovernmental organizations, and researchers include declining agricultural productivity, deforestation, introductions of non‐native flora and fauna, coastal erosion and sedimentation, damage to marine environments, illegal fishing, overfishing, waste pollution, salinization of freshwater supplies, and rising energy demands, among others. Human–environment challenges are connected to longer, often ignored, histories of social and ecological dynamics in the region. We argue that these challenges are more effectively understood and addressed within a longer‐term historical ecology framework. We reviewed cases from Madagascar, coastal Kenya, and the Zanzibar Archipelago of fisheries, deforestation, and management of human waste to encourage increased engagement among historical ecologists, conservation scientists, and policy makers. These case studies demonstrate that by widening the types and time depths of data sets we used to investigate and address current socioecological challenges, our interpretations of their causes and strategies for their mitigation varied significantly. Abstract : Article impact statement : Past human–environment dynamics are key to addressing today's threats to livelihoods and ecosystems in island and coastal southeast Africa.